Panorama de la gestión de la calidad académica universitaria - Albert Ypma (Revista Electrónica Educare)
Practical analysis of the role played by the staff in charge of the university's academic management. Three aspects are covered. First, a strategic view to discuss the Knowledge Society, the profile required of alumni in the work market and the European policy concerning Higher Education. Second, an outlook on quality, based on the management model from the European Foundation of Quality Management and the Deming cycle: planning, doing, measuring and improving. And finally, the stimulating role of academic management in developing an institutional pedagogical model to be applied in study programs, in the different teaching and learning methods, and developing an atmosphere of academic quality. The model is the result of exchanges carried out among coworkers of Universidad Nacional in the workshops organized by the MHO project Developing Institutional Quality , and also through other Dutch experiences.